Biosynthesis of iron oxide nanoparticles from dates, characterisation, and investigation of anticarcinogenic and antimicrobial properties - Kannan Kathiresan; Mani Ramakrishnan (Kuwait Journal of Science)
Nanoparticle synthesis using natural biological systems, especially plant-based green synthesis has evinced great excitement and interest. Iron oxide nanoparticles were synthesized from three different varieties of dates obtained from Srivilliputhur, Tamil Nadu, India. The extract of dates reduced ferric chloride in solution and facilitated the formation of iron oxide nanoparticles. Phytochemical studies of the extracts obtained from all three varieties of dates indicated the presence of phenols. The synthesized nanoparticles were characterized by UV-VIS spectroscopy, SEM, EDAX, XRD and FTIR methods. The ability of the synthesized nanoparticles to inhibit human microbial pathogens proliferation was tested in Staphylococcus sp. and Bacillus sp. by turbidity method and recorded the maximum antimicrobial property against Bacillus sp. in the iron nanoparticle synthesized from Sukhri dates. The cytotoxic potential of the iron oxide nanoparticles was assessed against two human cancer cell lines (A-549 and MDA-MB-231) by MTT assay. The substantial cytotoxicity response was detected from the Fe nanoparticles made from Sukhri dates.